DYNAMICS AND TYPOLOGY OF QURANIC CONTENT IN TIKTOK - Inayatul Mustautina Inaa; Saifuddin Zuhry Qudsy (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
Tik Tok has been considered as an attention grabbing alternative social media platform for the millennial generation as a way to convey and receive religious messages, especially Quranic messages. The use of TikTok as a new medium has also given birth to the current trend of learning the Qur’an. This study attempts to explain the impact of Quranic content on Tiktok on Quran learning. In the academic realm, this research seeks to contribute to discussions on the study of the Qur’an in its relation to social media. Using Ahmad Rafiq’s reception theory of the Qur’an and Gary R. Bunt’s theory of cyber Islamic environments, this qualitative research concludes the following points; first, the Quranic-related contents on TikTok comprise of several typologies, such as; quotes, interpretations, completing Quranic verses, tajwid, tahsin, qira’ah or recitations, lectures, news, stories, daily practices, murattal, rasm or manuscripts, the virtues of Quranic verses, memorization, guessing surahs, tips, and duets. Second, at the beginning of 2020, during the outbreak of COVID-19 pandemic, there had been an increased use of TikTok among people from various circles, ranging from the general public, celebrities, businessmen, preachers and others. Some preachers had been using TikTok as one of the learning media for the millennial generation. Third, TikTok had enabled creators of Quranic-related content to convey Quranic messages through Quranic content videos to be responded by netizens in the comments column. In this context, they started to turn to TikTok for religious advice and to answer some of their religious questions.